DESIGN OF STEEL SHELL FILLED WITH CONCRETE - , Ю. В. (Municipal economy of cities. Series: «Economy science», 2013)
We consider constructive forms of steel-concrete products and especially their work in a loaded condition. We study the strength and deformation of concrete in structures with external reinforcement. Recommendations on the use of reinforced concrete structures.